First report of Dryinus garcetei Olmi, 2012 (Hymenoptera, Dryinidae) in the Northeast region of Brazil - Marambaia, André L.; Ramos, Ramon L.; Trindade-Santos, Matheus E.; Martins, André L.; Oliveira, Favízia F. de; Santos, Rafaela L. da S. (Entomological Communications, 2024)
The present study reports the first record of Dryinus garcetei Olmi, 2012 (Hymenoptera, Dryinidae) for Northeast Brazil. This research is very relevant given the scarcity of data regarding the Dryinidae family and the Dryinus Latreille, 1804 genus for this region. Furthermore, illustrations and an updated geographic distribution map of D. garcetei are presented.